BH3 mimetics targeting BCL-XL impact the senescent compartment of pilocytic astrocytoma. Issue 4 (17th August 2022) - Selt, Florian; Sigaud, Romain; Valinciute, Gintvile; Sievers, Philipp; Zaman, Julia; Alcon, Clara; Schmid, Simone; Peterziel, Heike; Tsai, Jessica W; Guiho, Romain; Martínez-Barbera, Juan Pedro; Pusch, Stefan; et al.
Abstract: Background: Pilocytic astrocytoma (PA) is the most common pediatric brain tumor and a mitogen-activated protein kinase (MAPK)-driven disease. Oncogenic MAPK-signaling drives the majority of cells into oncogene-induced senescence (OIS). While OIS induces resistance to antiproliferative therapies, it represents a potential vulnerability exploitable by senolytic agents. Methods: We established new patient-derived PA cell lines that preserve molecular features of the primary tumors and can be studied in OIS and proliferation depending on expression or repression of the SV40 large T antigen. We determined expression of anti-apoptotic BCL-2 members in these models and primary PA. Dependence of senescent PA cells on anti-apoptotic BCL-2 members was investigated using a comprehensive set of BH3 mimetics. Results: Senescent PA cells upregulate BCL-XL upon senescence induction and show dependency on BCL-XL for survival. BH3 mimetics with high affinity for BCL-XL (BCL-XLi) reduce metabolic activity and induce mitochondrial apoptosis in senescent PA cells at nano-molar concentrations. In contrast, BH3 mimetics without BCL-XLi activity, conventional chemotherapy, and MEK inhibitors show no effect. Conclusions: Our data demonstrate that BCL-XL is critical for survival of senescent PA tumor cells and provides proof-of-principle for the use of clinically available BCL-XL-dependent senolytics.